2022
DOI: 10.3390/ijms232113139
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Degradation Study of Isomers in Human Plasma by HPLC-MS/MS and Application of LEDA Algorithm for Their Characterization

Abstract: This paper proposes a tandem mass spectrometry (MS/MS) approach in isomer recognition by playing in the “energetic dimension” of the experiment. The chromatographic set up (HPLC) was tuned to minimize the run time, without requiring high efficiency or resolution between the isomers. Then, the MS/MS properties were explored to solve the signal assignment by performing a series of energy resolved experiments in order to optimize the parameters, and by applying an interesting post-processing data elaboration tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…9,[15][16][17] Crotti et al have shown that accurate quantification of co-eluted isomers can be achieved by multilinear regression of ERMS. 9,[18][19][20][21] Complementary with the latter approach, Memboeuf et al have shown that ERMS and, more specifically, the survival yield (SY) plots can be used as a tool for detecting iso-baric/meric contamination. 15 Typically, SY curves of pure compounds are sigmoidal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[15][16][17] Crotti et al have shown that accurate quantification of co-eluted isomers can be achieved by multilinear regression of ERMS. 9,[18][19][20][21] Complementary with the latter approach, Memboeuf et al have shown that ERMS and, more specifically, the survival yield (SY) plots can be used as a tool for detecting iso-baric/meric contamination. 15 Typically, SY curves of pure compounds are sigmoidal.…”
Section: Introductionmentioning
confidence: 99%
“…Although other techniques have been developed to analyse iso‐baric/meric mixtures, such as the kinetic method 7–10 and, more recently, ion mobility mass spectrometry (MS), 9,11–14 energy‐resolved mass spectrometry (ERMS) can also provide reliable results for quantitative analysis in the presence of iso‐meric/baric interferences 9,15–17 . Crotti et al have shown that accurate quantification of co‐eluted isomers can be achieved by multilinear regression of ERMS 9,18–21 . Complementary with the latter approach, Memboeuf et al have shown that ERMS and, more specifically, the survival yield (SY) plots can be used as a tool for detecting iso‐baric/meric contamination 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Then, the same HPLC conditions can be used with a large number of analytes without worrying about their separation, and the LEDA elaboration of the MS/MS data assures the signal distinction of the compounds. The reliability of this procedure allowed us to carry out a kinetic study on the enzymatic hydrolysis of a pair of isomers present simultaneously in plasma samples, evaluating their different degradation profiles [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the collision energy increases the internal energy of the colliding ions, and that in turn increases the degree of fragmentation, changes the ratio of various fragment ion abundances, and may also change fragmentation routes. Varying and optimizing the collision energy has various practical applications, such as determination of binding energies [ 8 , 9 ], differentiation of isomers [ 10 , 11 , 12 ], characterization of oligonucleotides [ 13 ] and small molecules [ 14 , 15 , 16 , 17 ], and various proteomic applications [ 18 , 19 , 20 ] including quantitation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%